Mitigating Uremic Pruritus and Improving Family Coping in Stage 5 Chronic Kidney Disease: A Dual-Intervention Case Study Using Topical Petrolatum - Anggia Astuti Astuti; Luluk Sofia Davina Astuti; Zainal Abidin; Rizeki Dwi Fibriansari (KHD Production, 2026)
Chronic Kidney Disease (CKD) imposes severe physical and psychosocial burdens, frequently precipitating a measurable decline in family coping mechanisms. This study explores the clinical efficacy of a dual intervention combining structured family coping support and topical petroleum jelly therapy for managing uremic pruritus and caregiver strain. Employing a descriptive case study design, researchers intervened with the family of a 55-year-old male diagnosed with stage 5 CKD who presented with severe pruritus, xerosis, and skin discoloration. The family initially exhibited care neglect, limited communication, and inadequate health literacy regarding appropriate symptom management. The protocol entailed targeted coping support education, along with twice-daily petroleum jelly application over eight consecutive days. Outcome measurements utilized the validated 5D Pruritus Scale and standardized nursing criteria to evaluate family coping. Post-intervention data revealed a significant reduction in the 5D Pruritus Scale score from 10 to 6, indicating a clear transition to mild pruritus. Family assessments concurrently demonstrated substantial improvements in health knowledge, active caregiving engagement, and interpersonal communication, effectively eliminating previous neglectful behaviors. These findings establish that integrating low-cost topical emollient therapy with targeted psychosocial education constitutes a highly effective, holistic nursing strategy. This comprehensive approach successfully mitigates dermatological distress while simultaneously restoring family coping capacity, offering a highly replicable model for advanced CKD management in community health settings.